2017
DOI: 10.1016/j.jhsa.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study of Insertional Anatomy of Distal Biceps Tendon and its Relationship to the Dynamic Proximal Radioulnar Space

Abstract: Postoperative DBT impingement in the RUS may be prevented by avoiding techniques that increase the thickness of the tendon and by using a reattachment site at the proximal aspect of the tuberosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
0
29
0
6
Order By: Relevance
“…In the largest series with 50 cadavers, Joshi found an average tendon length of 7.6cm and no side difference [ 14 ]. But he did not distinguish between sex and body size, as almost all other anatomical studies [ 12 , 13 , 15 ]. Only Shastry et al differentiated between 10 female and 14 male cadavers [ 16 ].…”
Section: Discussionmentioning
confidence: 96%
“…In the largest series with 50 cadavers, Joshi found an average tendon length of 7.6cm and no side difference [ 14 ]. But he did not distinguish between sex and body size, as almost all other anatomical studies [ 12 , 13 , 15 ]. Only Shastry et al differentiated between 10 female and 14 male cadavers [ 16 ].…”
Section: Discussionmentioning
confidence: 96%
“…A clear understanding of these anatomic variations and its relationship with radial tuberosity is vital in planning and performing a distal biceps tendon repair and also in determining if a graft is required to supplement or replace the native tendon. There are studies done previously which describe the gross morphological anatomy of the distal biceps with main focus on distal footprint types and characteristics (7,8). But these studies do not give the normal morphometric measurements of the tendon.…”
Section: Discussionmentioning
confidence: 99%
“…4 The importance of the radio-ulnar space has also been demonstrated by the study by Bhatia that demonstrated that the spaced reduces significantly from the fully supinated to the fully pronated position. 5 This elliptic form also has its consequence of the humero-radial joint. From biomechanical point of view, it has been described that different orientations of the longest axis of the noncircular radial head will result in different forces in the humero-radial joint.…”
Section: Discussionmentioning
confidence: 99%